Dry matter intake, methane emissions and microbiome profiles as new traits for feed efficiency - López Paredes, Javier (2021)
This study estimated the genetic parameters for feed efficiency, dry matter intake, methane production, and ruminal microbiome profile in order to incorporate feed efficiency into the breeding goal. Data consisted of 11,042 weekly averaged records for dry matter obtained from 551 cows in 5 farms, as well as 4,624 methane emission measurements using a non-dispersive infrared methane detector installed within the feed bin of the automatic milking system during 14 to 21 days period from 1,501 cows in 14 farms. In addition, ruminal content was extracted from 437 cows with methane phenotypes. Data for milk yield, protein yield, fat yield, fertility, body depth, rump width, chest width and predicted live weight from 11,228 cows were included in the analysis. Heritability and genetic correlations were estimated from bivariate models within a single step framework using AIREML. The heritability estimate for dry matter intake was moderate (0.16±0.03), with a genetic correlation with milk yield of 0.41 (0.11), and with type traits ranging from 0.25 to 0.49. Heritability estimates for methane production (0.17±0.05) and methane concentration (0.18±0.04) were moderate, and their genetic correlations with milk yield were close to zero (-0.05±0.11 and 0.04±0.11). Higher genetic correlations were estimated with type traits, ranging from 0.14 to 0.59. Genetic correlations between methane traits and dry matter intake were positive and ranged from 0.20±0.48 to 0.27±0.43. This suggests a correlated response in methane emissions when selecting for more ravenous animals. The microbiome aggregated variables showed higher positive genetic correlation with methane traits (0.53±0.19 and 0.87±0.19), and dry matter intake (0.32±0.36). These results highlight an important interrelationship between methane production and dry matter intake, with a significant role of the microbiome composition. The results suggest that selecting cows that make a more efficient utilization of energy intake is feasible through selection on correlated type traits such as body capacity, stature, and body depth, without compromising high productive performance. Selection for lower methane emissions is expected to have similar results. The inclusion of the microbiome composition may assist on a more efficient selection on both, lower emissions and higher feed efficiency. However, proper weights must be applied in the selection indices to maintain current genetic trends on productive and functional traits.